The Role of Trade Unions in Determining and Supervising Compliance with Occupational Health and Safety Standards - Latos-Miłkowska, Monika (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
Protecting the life and health of employees, implemented through the principles of occupational health and safety, is one of the most important tasks of company trade unions. In order to enable company trade unions to carry out this task, the legislator has provided them with a number of competencies. These competencies – divided into regulatory powers and control powers – are the subject of analysis in this article. The purpose of undertaken analysis is to evaluate the adequacy of the solutions adopted by the legislator in this area and to indicate possible de lege ferenda changes aimed at strengthening the position of company trade unions organisations in this extremely important sphere.